Etiological Spectrum of Pancytopenia in Children of Southern Punjab - Zill-E-Rubab, Jawad Zaffar Choudry, Asma Naseer Cheema, Zulfiqar Ali Rana, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pancytopenia is an intermittent hematological finding in children presenting with erratic clinical features like fever, pallor, petechiae, bleeding, distended abdomen, failure to thrive. Aim: To evaluate the pattern of causes responsible for pancytopenia in children of southern Punjab. Study Design: Randomized control trail. Methodology: We enrolled 121 children, aged 1-15 years with pancytopenia after written informed consent for a period of one year in Pathology department of Children’s Hospital-Multan. Cell morphology was studied through microscopy on blood peripheral film and bone marrow aspiration film. The relevant investigations were performed to assess the pattern of causative agents in pediatric population of Southern Punjab, Pakistan. Data was presented as percentage through SPSS v20.0. Results: Fever, pallor and body-aches were the common (80%) clinical presentations in our patients. Mean ± SD age of patients was 7.1± 3.98 years. 56.50% of patients with pancytopenia had hyper-cellular marrow while 43.50% had hypo- cellular marrow. Aplastic anemia and Acute Lymphoblastic Leukemia were the common causes for pancytopenia. Conclusion: We concluded that aplastic anemia and ALL were the most common causes of pancytopenia in Southern Punjab, Pakistan. Infections and other treatable causes were also important causes of thrombocytopenia present in significant number (21.7%) of patients which we can address timely and reverse the serious outcomes. Keywords: Anemia, Bone Marrow, Megaloblastic and Pancytopenia.